Analisis Perilaku Konsumen Menggunakan Market Basket Analysis Pada Unit Usaha Koperasi As-Sakinah ‘Aisyiyah Jember - Yanuarti, Rosita; Amiri, Yusril Izzi Arlisa (INFORMAL: Informatics Journal, 2024)
As an economic enterprise based on the interests and welfare of members, the business units that have been implemented by As-Sakinah Cooperative include providing and fulfilling the basic needs of members. Therefore, in 2012 As-Sakinah Cooperative established the Toko As-Sakinah business unit. This business unit aims to provide the basic needs of members, as well as the needs of Muhammadiyah, 'Aisyiyah and other organizations. Not only that, the As-Sakinah Cooperative business unit also acts as a place for marketing the products of the economic efforts of 'Aisyiyah members. The importance of consumer behavior analysis using market basket analysis on sales transactions of the As-Sakinah Store business unit is as a marketing strategy to increase sales transactions by looking at consumer behavior patterns towards the relationship between products based on purchase transactions made by members and other customers. In addition, the results of this market basket analysis can also be used for marketing strategies and data-based decision making. Market basket analysis or shopping basket analysis is an analysis of customer behavior in conducting buying and selling transaction activities. Shopping basket analysis produces findings of association or connection between one item and another, where these items are in one customer's basket. The results of this research indicate that with a minimum support value of 5% and a minimum confidence of 5% it produces 11 rules, where the pattern of associations between items found has a very high association tendency. The resulting association rules also show low variation, this is influenced by the small variation of transactions made by customers. From the rules generated, it can be seen that not many product combinations are obtained, this is because most of the sales transactions consist of only one product purchased by customers. So that the effectiveness of the application of market basket analysis in this cooperative is not optimal